2017
DOI: 10.1007/s10068-017-0244-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity and partial characterization of proteases obtained from Bromelia karatas fruit and compared with Bromelia pinguin proteases

Abstract: The enzymatic activity and partial characterization of proteases from fruits were evaluated and compared with proteases. The specific activity increased twofold after partial purification in both proteases. Partially purified proteases from showed good specific activity at pH 6.0-8.0 and residual activity of 70-100% for 60 min at 37-60 °C, similar to proteases. The value of proteases from was higher (253.32 µM) than that of proteases (234.94 µM). The use of specific protease inhibitors indicated the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…The reported proteolytic activity of proteases from B. pinguin and B. karatas fruits is variable; for example, for proteases from B. pinguin extract, the reported values were 11 U cas /mL [6], 2.31 U cas /mg [8], 0.98 U cas /mL [16], 3.2 U/mg [17], while for proteases from B. karatas extract, the reported value was 1.2 azocol/mg min/mL [10]. In this work, the proteolytic activity of the concentrated proteases was 21.93 U T for proteases from B. karatas and 43.58 U T for proteases from B. pinguin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported proteolytic activity of proteases from B. pinguin and B. karatas fruits is variable; for example, for proteases from B. pinguin extract, the reported values were 11 U cas /mL [6], 2.31 U cas /mg [8], 0.98 U cas /mL [16], 3.2 U/mg [17], while for proteases from B. karatas extract, the reported value was 1.2 azocol/mg min/mL [10]. In this work, the proteolytic activity of the concentrated proteases was 21.93 U T for proteases from B. karatas and 43.58 U T for proteases from B. pinguin.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that pinguinain has a molecular mass (MM) of 20 kDa [7]. In a recent study by Meza-Espinoza et al [8], K m values for B. karatas and B. pinguin were determined; Moreno-Hernández et al [9] demonstrated that crude enzymatic extracts from B. pinguin fruit showed high proteolytic properties; the proteases had adequate stability to oxidizing agents, reducing agents and organic solvents. On the other hand, Montes et al [10] extracted proteases from B. plumieri (karatas) fruits and named a protein fraction karatasin with a MM of 24.86 kDa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El efecto del tiempo se debe a que las proteasas a 120 min, causaron seguramente un mayor porcentaje de hidrólisis proteíco. Se ha reportado que a mayor grado de hidrólisis, mayor es la variabilidad en tamaño de PB (Meza-Espinoza et al, 2017); así, su funcionalidad o bioactividad puede aumentar debido a que se pueden presentar efectos sinérgicos en la eliminación de los radicales libres y por ende ocurra una mayor actividad de IHO (Klompong, Benjakul, Kantachote & Shahidi, 2007). Las diferencias en la IHO dependiente de las proteasas extraídas por especie vegetal y sustratos usados (p<0.05), se atribuye a la especificidad de cada proteasa, por ende, cada una puede producir hidrolizados con diferentes tamaños de péptidos con diferente composición de aminoácidos (Vioque et al, 2006).…”
Section: Inhibición De Hemólisis Oxidativa (Iho)unclassified
“…Las proteasas específicas más utilizadas para generar PB son las microbianas; sin embargo, el uso de proteasas vegetales en la hidrólisis de proteínas se ha incrementado en los últimos años debido a su estabilidad en un amplio rango de pH y temperatura (Moreno-Hernández et al, 2017). Las proteasas extraídas de frutos de Bromelia karatas (B. karatas) y Bromelia pinguin (B. pinguin) no han sido estudiadas para generar PB; no obstante, de acuerdo a estudios previos, estas proteasas presentan una alta actividad proteolítica, con un grado de hidrólisis de 73-80% (Meza-Espinoza et al, 2017) por lo tanto, son potenciales para la generación de PB.…”
unclassified